Growth arrest-specific 6 in chromophobe renal cell carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Erlmeier, Maximilian; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (Oncology, 2022)
Overexpression of tumor-associated growth arrest-specific protein 6 (Gas6) is found in many tumor entities. The prognostic value of Gas6 in renal cell carcinoma (RCC), especially in non-clear cell RCC, is still unclear. The aim of the study was to evaluate the prognostic impact of Gas6 expression in a large cohort of patients with chromophobe RCC (chRCC).
Gesehen am 10.01.2023